Síntese verde da zeólita ZSM-5 assistida por micro-ondas e aplicação na rota de pirólise catalítica do óleo de fritura e sebo bovino - Caldas, Amanda Menezes (2024)
Catalysis plays a fundamental role in the current energy transition, enabling efficient biomass conversion. Zeolitic materials are among the heterogeneous catalysts widely explored in the industry, including petrochemicals, due to their high activity, selectivity, and thermal stability. In this class, zeolite ZSM-5 stands out, which has a porous structure, which gives it the characteristics of a molecular sieve, capable of selectively adsorbing molecules. The hydrothermal process is the most commonly used for the synthesis of this catalyst, where crystallization times of up to 72 hours are reported, in addition to the use of organic template and/or seeds to obtain the crystalline structure. Based on this, this work explored an innovative method without organic template and no seedless, assisted by microwaves, to obtain zeolite ZSM-5. The method allowed the formation of the crystalline structure in a period of up to 10 hours, depending on the conditions, and proved to be an efficient alternative by providing savings in time, reagents, energy, and total costs. The applicability of the catalyst was explored for the thermal conversion of residual biomass from frying oil (OF) and beef tallow (SB) from the catalytic pyrolysis process, in their protonated (HZSM-5) and nickel-impregnated (Ni/HZSM-5) forms. The samples were characterized, enabling confirmation of the formation of the stable orthorhombic structure and structural preservation. The OFW and KAS kinetic studies were proposed, which demonstrated the decrease in activation energies (Ea), provided by the catalysts. The results obtained from the catalytic pyrolysis tests confirmed the performance of the catalysts for the cracking of hydrocarbons, and selectivity for C10 to C14 fractions, with profiles that favor the production of biokerosene. The deoxygenation promoted by the catalysts was higher with Ni/HZSM-5, where oxygenated percentages of 7.8% were obtained for the frying oil and 1.3% for the beef tallow, demonstrating the influence of bifunctionality due to the addition of the metal. Pyrolysis-coupled chromatography analyses demonstrated a reduction in oxygenated products in the catalyzed processes, and the aromatization effect, especially for the frying oil biomass due to the unsaturations present in its chemical structure. Thus, the work is presented in order to contribute to sustainable development through two aspects: through the promising sustainable method of synthesis of the ZSM-5 zeolite, and through the waste stream.